Digital Transformation Acceleration Policy in Indonesia (Study on the Implementation of all in One Indramayu Information Technology in Indramayu Regency) - Ibrahim, Ibrahim (Formosa Journal of Applied Sciences, 2023)
Technology plays an important role in keeping society's activities running as they should. The practice of using information technology for the community is directed at increasing the reliability of community service technology, the effectiveness and efficiency of receiving services by the community. This study uses descriptive qualitative, where in data collection using secondary data in the form of documentation at the research location. The data analysis technique is a descriptive analysis technique, in which the analysis is carried out to be able to explain the Application of All In One Information Technology in Improving Public Services in Indramayu Regency. The results of the research show that the application of All In One Information Technology in Indramayu Regency. There are several inhibiting factors both in socialization and application implementation including internal and external factors, internal factors.